Simulation of APM AC Traction Power Supply System - Cuie ZHANG; Ping SHEN; Yin WANG; Shunying XIA (机车电传动)
At present, the theoretical research on APM (Automated People Mover) traction power supply system is not mature in China. In order to assist in the design of new APM line, based on the analysis of the existing APM traction power supply system, Simulink was used to model the components of its external power supply, traction substation, three-phase contact rail and vehicle. The voltage distribution of contact rail during normal operation and overload operation of the train was compared and analyzed to verify the correctness of the established simulation model of APM AC traction power supply system. The simulation analyzed the influence of different tracking distances on the electrical characteristics of the system when two trains were running at the same time. The voltage distribution on the contact rail when the single substation was out of operation was analyzed, and the security and reliability of the system power supply were verified, which provided the basis for the setting and selection for the APM pre-power supply scheme.